Kajian Kerusakan dan Penanganan Derajat Kemiringan Propeller CPP pada Kapal Tanker MT. Keoje Kirin - Afdolludin Afta Tazani (Politeknik Bumi Akpelni Semarang, 2025)
A Controllable Pitch Propeller (CPP) is a propeller that can adjust its pitch as needed for forward or reverse movement through a hydraulic oil system. The condition of components within the CPP system greatly affects propeller performance; damage to a single component can disrupt operation, necessitating regular maintenance. This study uses a combined SHEL and USG method to analyze the factors causing the propeller to not function optimally, the impact, and mitigation efforts. The study was conducted on the MT. Keoje Kirin vessel (August 31, 2016 – October 23, 2017) and identified four main factors causing the issues: malfunctioning Oil Distribution Box (ODB), a tight operational schedule, lack of crew skills, and suboptimal implementation of Standard Operating Procedures (SOPs). Recommended solutions include scheduled PMS maintenance, ODB repairs, laboratory testing of hydraulic fluid quality, crew training before boarding, and the development and implementation of appropriate SOPs.